The Relationship between Aggression and Impulsiveness with Susceptibility for Addiction in Male Student - Younes Doustian; Bahman Bahmani; Yousef A'zami; Ali Akbar Godini (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: The present study examined the relationship of aggression and impulsiveness with readiness for addiction among the students of Allameh Tabatabai University. Materials & Methods: The methodology applied in this research was cross- analytical. 170 male undergraduate students who study at Allameh Tabataba'i University were selected by two-stage random sampling. To measure the variables, Aggression Questionnaire of Ahvaz, Barrat Impulsiveness scale(BIS) and the readiness for addiction scale of Wade and Butcher were employed. To analyze the findings, the Pearson correlation coefficient and multiple regressions were used. Results: Results indicated that the variables of aggression and impulsiveness were significantly able to predict the readiness for addiction (P<0.001). Also, based on the coefficient of determination, aggression and impulsiveness variables together predicted 49 percent of variance of addiction readiness variable. Conclusion: Noting that the variables of aggression and impulsivity can properly predict readiness for addiction, university counseling centers can, through workshops, teach the students different ways of controlling these variables in a variety of situations and so they will be able to prevent the tendency towards drug use.